2022
DOI: 10.1186/s12883-022-02734-x
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of functional outcome in poor-grade aneurysmal subarachnoid hemorrhage: a systematic review and meta-analysis

Abstract: Background Patients with poor-grade aneurysmal subarachnoid hemorrhage (aSAH) often receive delayed or no aneurysm treatment, although recent studies suggest that functional outcome following early aneurysm treatment has improved. We aimed to systematically review and meta-analyze early predictors of functional outcome in poor-grade aSAH patients.  Methods We included studies investigating the association of early predictors and functional outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Several studies in the literature support the fact that IVH ( 25 ) and ICH ( 16 , 18 , 26 ) are negative and critical prognostic factors in aSAH. Compared to the subarachnoid counterpart, we found out that routine analysis of IVH and ICH fractions is a simple, fast and relatively easy-to-learn method for quantitative assessment of the hemorrhagic load on the initial CT scan.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Several studies in the literature support the fact that IVH ( 25 ) and ICH ( 16 , 18 , 26 ) are negative and critical prognostic factors in aSAH. Compared to the subarachnoid counterpart, we found out that routine analysis of IVH and ICH fractions is a simple, fast and relatively easy-to-learn method for quantitative assessment of the hemorrhagic load on the initial CT scan.…”
Section: Discussionmentioning
confidence: 87%
“…Notably, in 2022 de Winkel et al published a systematic review and meta-analysis ( 18 ) on early predictors of functional outcome in poor-grade aSAH. This analysis revealed that WFNS grade or Hunt and Hess (HH) grade IV, presence of clinical improvement before aneurysm treatment and intact pupillary light reflex were associated with the likelihood of favorable outcome, while, older age, increasing modified Fisher grade and the presence of intracerebral hematoma on admission imaging decreased the possibility of favorable outcome ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral vasospasm and delayed cerebral ischemia (DCI) are major factors for survival and functional outcome following SAH and have, for many years, been the main focus in SAH research [ 42 , 43 , 44 , 45 ]. Clinical parameters such as Hunt and Hess scores, lower modified Fisher grade, the absence of intracerebral hematoma, intact pupillary light reflexes, and clinical improvement before aneurysm treatment can be used as early clinical predictors of functional outcome and favorable/non-favorable prognosis [ 46 ]. However, other factors such as inflammation have also been shown to be useful predictors of poor outcome in patients with SAH.…”
Section: Discussionmentioning
confidence: 99%
“…IV-V) being associated with poor prognosis [ 7 ]. Nevertheless, different studies have shown that more than 20% of patients with high grade WFNS treated aggressively can recover completely, making initial resuscitation decisions very challenging for clinicians [ 8 , 9 ]. With the aim of improving the prognostic accuracy of patients affected by SAH, modifications of WFNS scale [ 10 ], assessment of the WFNS scale after initial resuscitation [ 9 ] as well as different combined scores [ 11 , 12 ] have been proposed.…”
Section: Introductionmentioning
confidence: 99%